2017
DOI: 10.1016/j.metabol.2017.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma metabolomics in adults with cystic fibrosis during a pulmonary exacerbation: A pilot randomized study of high-dose vitamin D 3 administration

Abstract: Background Cystic fibrosis (CF) is a chronic catabolic disease often requiring hospitalization for acute episodes of worsening pulmonary exacerbations. Limited data suggest that vitamin D may have beneficial clinical effects, but the impact of vitamin D on systemic metabolism in this setting is unknown. Objective We used high-resolution metabolomics (HRM) to assess the impact of baseline vitamin D status and high-dose vitamin D3 administration on systemic metabolism in adults with CF with an acute pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…This would support a targeted approach which may be useful for metabolic monitoring of treatment responses. Our findings related to pulmonary exacerbation are consistent with other CF metabolomics studies that demonstrate specific patterns related to exacerbation …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would support a targeted approach which may be useful for metabolic monitoring of treatment responses. Our findings related to pulmonary exacerbation are consistent with other CF metabolomics studies that demonstrate specific patterns related to exacerbation …”
Section: Discussionsupporting
confidence: 92%
“…Our findings related to pulmonary exacerbation are consistent with other CF metabolomics studies that demonstrate specific patterns related to exacerbation. 30,[36][37][38][39] Significant expertise was needed to develop and complete this study with high level coordination, but we were limited to a single-center cohort of adolescents and adults. Additionally, a lack of comparison to subjects initiating Ivacaftor alone or not initiating therapy, fixed length of treatment follow-up, variable diets, and lack of culture-independent microbiome data availability hinder further comparisons.…”
Section: Metabolites Correlate With Clinical Responsementioning
confidence: 99%
“…Even though mechanistic studies mostly were done in vitro, few studies in human suggest that the positive effects of vitamin D on exacerbations in CF are mostly attributed to its immunomodulatory properties as reflected by reduced serum IL-6, TNF levels [61], and IL-8 levels [66] or reduced serum Ig(G) levels [45]. A study on metabolomics on plasma of a supplemented CF population revealed that the beneficial effects of high-dose vitamin D in hospitalized CF adults with an acute pulmonary exacerbation may have occurred through a metabolic stabilization of amino acids, lipids, and other metabolites [67].…”
Section: Vitamin D In Cystic Fibrosismentioning
confidence: 99%
“…Metabolomic approaches are increasingly used in the study of diabetes, dyslipidemia, cancer, chronic neurological disorders, pharmaceutics, and nutrition to name a few. Research into the metabotype of individuals during the disease processes has led to new biomarkers of disease status as well as new targets for interventions and the impact of nutritional interventions (Alvarez et al, 2017; McGrath & Young, 2015). Nutritional metabolomics is seeking to identify novel biomarkers of dietary intake to provide objective measures of dietary intake (Schmidt et al, 2015).…”
Section: Nursing Science Exemplar: Metabolomicsmentioning
confidence: 99%
“…Hypotheses of how diet may improve MS include reduction of inflammation, alteration of the microbiome, increased nutrient provision for cellular healing, epigenetic changes, increased mitochondrial function, among others. Currently, Grossmann and colleagues use a multi-omics approach (metabolome, microbiome and epigenome analyses) to identify potential biomarkers as well as to gain insights into mechanisms related to dietary interventions in MS and cystic fibrosis(Alvarez et al, 2017). …”
Section: Nursing Science Exemplar: Metabolomicsmentioning
confidence: 99%